2013
DOI: 10.1155/2013/914563
|View full text |Cite
|
Sign up to set email alerts
|

Dried Ginger (Zingiber officinalis) Inhibits Inflammation in a Lipopolysaccharide-Induced Mouse Model

Abstract: Objectives. Ginger rhizomes have a long history of human use, especially with regards to their anti-inflammatory properties. However, the mechanisms by which ginger acts on lipopolysaccharide-(LPS-)induced inflammation have not yet been identified. We investigated the anti-inflammatory effects of dried Zingiber officinalis (DZO) on LPS-induced hepatic injury. Methods. ICR mice were given a DZO water extract (100, 1000 mg/kg) orally for three consecutive days. On the third day, they were administered by LPS int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 26 publications
3
44
0
Order By: Relevance
“…In addition, ginger inhibited LPS-induced activation of NF-κB by preventing the degradation of the IκBα, as well as the phosphorylation of ERK1/2, SAPK/JNK and p38 MAPKs [53]. A strong decrease in the expression of iNOS and COX-2 were also observed [53]. Together all these observations clearly indicate that ginger modulating myriad pathways, and thereby, affords the anti-inflammatory effects.…”
Section: Ginger Possesses Anti-inflammatory Effectsmentioning
confidence: 82%
See 2 more Smart Citations
“…In addition, ginger inhibited LPS-induced activation of NF-κB by preventing the degradation of the IκBα, as well as the phosphorylation of ERK1/2, SAPK/JNK and p38 MAPKs [53]. A strong decrease in the expression of iNOS and COX-2 were also observed [53]. Together all these observations clearly indicate that ginger modulating myriad pathways, and thereby, affords the anti-inflammatory effects.…”
Section: Ginger Possesses Anti-inflammatory Effectsmentioning
confidence: 82%
“…Seminal studies by Choi et al [53] have shown that ginger inhibits the LPS-induced inflammation in ICR mouse. The investigators observed that the oral administration of the aqueous extract of dried ginger (100 or 1000 mg/kg) for three consecutive days was effective in reducing the LPS-induced pathological changes in the liver, and to decrease the levels of proinflammatory cytokines like IFN-γ and IL-6 in the serum [53].…”
Section: Ginger Possesses Anti-inflammatory Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginger acts as anti-parasitic; study shows the in vivo potential of methanolic extract of Zingiber officinale in the treatment of trypanosomiasis (Halvorsen et al, 2002;Jagetia et al, 2003;Kubra et al, 2013;Duarte, 2016;Kumar et al, 2015;Choi et al, 2013;Saraswat, 2010;Pushpanathan, 2008).…”
Section: Antiparasitic Actionmentioning
confidence: 99%
“…The mineral element of ginger is effective for the same (El-Sharaky et al, 2009;El-Abhar et al, 2008;Jagetia et al, 2004;Choi et al, 2013 ;Pushpanathan, 2008).…”
Section: Insulinmentioning
confidence: 99%